Suppression of influenza virus infection by an N-thioacetylneuraminic acid acrylamide copolymer resistant to neuraminidase - Itoh, Masae; Hetterich, Peter; Isecke, Rainer; Brossmer, Reinhard; Klenk, Hans-Dieter (Virology, 1995)
We have previously shown that α-2-O-methyl-5-N-thioacetylneuraminic acid (α-Neu5thioAc2Me) has a higher affinity to bromelain-treated hemagglutinin (HA) of influenza A virus than sialic acid from natural sources (Machytka et al., 1993, FEBS Lett. 334, 117-120). We have now compared the inhibitory effects of α-Neu5thioAc2Me and other sialic acid analogs on receptor binding and plaque formation of intact influenza A viruses. When α-Neu5thioAc2Me was polymerized by conjugation to polyacrylamide, its affinity to HA increased 103-fold. When analyzed by plaque reduction, the α-Neu5thioAc2 polymer was about 10 times more efficient as an inhibitor of virus replication than the α-Neu5Ac2 polymer, stressing the importance of sulfur at C5. The S-glycoside α-2-S-methyl-5-N-thioacetylneuraminic acid (α-Neu5thioAc2SMe) had the same affinity to HA as α-Neu5thioAc2Me, but was resistant to neuraminidase. The α-Neu5thioAc2S polymer interfered with the replication of a wider spectrum of influenza A virus subtypes than the α-Neu5thioAc2 polymer. The results indicate that the αNeu5thioAc2S polymer has the potential to be used as an inhibitor of influenza virus infection.